Ответы и объяснения

2013-01-20T00:51:05+04:00

(    x+3y      +          3      )*9y^3-x^2y  =(  x+3y       3     )   *  y(9y^2-x^2)  =

  x^2y-3xy^2     x^2+3xy     (9y+x)^2       xy(x-3y)    x(x+3y)       (9y+x)^2

=x^2+6xy+9y^2+3yx-9y^2  *  y(9y^2-x^2)            =      x(x+9y)             *  y(9y^2-x^2)           =

          xy(x-3y)(x+3y)                (9y+x)^2                        xy(x-3y)(x+3y)          (9y+x)^2    

=             x              *  y(9y^2-x^2)           =        9y^2-x^2            =       9y^2-x^2          =

      xy(x-3y)(x+3y)       9y+x                        (x-3y)(x+3y)(9y+x)     (x^2-9y^2)(9y+x)

=  выносим - за скобку,получается -   1          

                                                                     9y+x
Как то так.